2012
DOI: 10.1371/journal.pone.0051658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Uric Acid Levels following Bariatric Surgery Are Not Associated with SLC2A9 Variants in the Swedish Obese Subjects Study

Abstract: Context and ObjectiveObesity and SLC2A9 genotype are strong determinants of uric acid levels. However, data on SLC2A9 variants and weight loss induced changes in uric acid levels are missing. We examined whether the changes in uric acid levels two- and ten-years after weight loss induced by bariatric surgery were associated with SLC2A9 single nucleotide polymorphisms (SNPs) in the Swedish Obese Subjects study.MethodsSNPs (N = 14) identified by genome-wide association studies and exonic SNPs in the SLC2A9 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
4
2
Order By: Relevance
“…In particular, we did not find any correlation between improved insulin resistance, as assessed by the HOMA-IR, and reduced SUA levels. Contrary to what is generally accepted to be true (16,25), this lack of correlation, also reported in another study (14), suggests that reduced SUA levels after bariatric surgery may not be explicable by increased uric acid renal clearance resulting from the improved insulin resistance in such patients (25).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In particular, we did not find any correlation between improved insulin resistance, as assessed by the HOMA-IR, and reduced SUA levels. Contrary to what is generally accepted to be true (16,25), this lack of correlation, also reported in another study (14), suggests that reduced SUA levels after bariatric surgery may not be explicable by increased uric acid renal clearance resulting from the improved insulin resistance in such patients (25).…”
Section: Discussioncontrasting
confidence: 67%
“…The SLC2A9 variants, known to be closely associated with SUA levels (23,24), were recently found to have no role in changed SUA levels in response to weight loss after bariatric surgery (25).…”
Section: Discussionmentioning
confidence: 99%
“…Our reliance on the simple formula h 2 = 2 β OP /(1 + r spouse ) and h 2 = {(1 + 8 r spouse β FS ) 0.05 − 1}/(2 r spouse ) to estimate heritability [ 32 ] is unlikely to embody the true complexity of uric acid inheritance. Our reinterpretations of the results presented by Das Gupta et al [ 37 ], Yang et al [ 42 , 51 ], Lin et al [ 43 ], Sarzynski et al [ 47 ], Cheng et al [ 48 ], Brandstätter et al [ 49 ], and Hamajima and colleagues [ 52 ] do not disprove their original explanations, rather they suggest an alternative interpretation that warrants consideration.…”
Section: Discussioncontrasting
confidence: 54%
“…Bariatric surgery reduces serum uric acid concentrations. Sarzynski et al [ 47 ] reported that uric acid reductions following bariatric surgery were affected by SLC2A9 rs13113918, a coding SNP that produces a synonymous substitution (Leu79Leu). Specifically, the histogram in Figure 3(e) (estimated from their figure 2 ) shows that the number of rs13113918 minor (A) alleles significantly affected two-year decreases in uric acid concentrations after 29 kg weight loss ( P interaction = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…The underlined genetic variants were found in our cohort. References to studies relating to genetic variants in this figure: p. R294H and p.I168I [ 22 ], p.L108L [ 31 ], c.535 + 67A > G [ 23 ], p.N82N [ 18 ], p.H86H [ 19 ], p.C258T and p.C426T [ 32 ], p.L75R [ 33 ], p.T125M [ 34 ], p.R171H [ 35 ], p.T467M and p.L415_G417del [ 29 ], p.R434M [ 36 ]. Foot and kidney images were copied from Servier Medical Art, by Servier ( ; kidney image: ; foot image: ) and adapted for the purposes of this article.…”
Section: Figurementioning
confidence: 99%